Levels of antibody to conserved parts of plasmodium falciparum merozoite surface protein I in Ghanaian children are not associated with protection from clinical malaria. - Dodoo, D.; Theander, T.G.; Kurtzhals, J.A.L.; Koram, K.A.; Riley, E.; Akanmori, B.D.; Nkrumah, F.K.; Hviid, L. (Infection and Immunity, 1999)
The 19-kDa conserved C-terminal part of the Plasmodium falcifarum merozoite surface protein 1 (PfMSP1 19) is a malaria vaccine candidate antigen, and human antibody responses to PfMSP1 19 have been associated with protection against clinical malaria. In this longitudinal study carried out in an area of stable but seasonal malaria transmission with an estimated parasite inoculation of about 20 infective bites/year, we monitored 266 3-to 15-year-old Ghanaian children clinically and parasitologically over a period of 18 months. Blood samples were collected at the beginning of the study before the major malaria season in April and after the season in November. Using enzyme-linked immunosorbent assay, we measured antibody responses to recombinant gluthathione S-transferase-PfMSP1 19 fusion proteins corresponding to the Wellcome and MAD20 allelic variants in these samples. Prevalence of antibodies recognizing the Wellcome 19 construct containing both epidermal growth factor (EGF)-like motifs in Wellcome type PfMSP1 19 was about 30%. Prevalence of antibodies to constructs containing only the first EGF domain from either Wellcome or MAD20 type PfMSP1 19 was about 15%, whereas antibodies recognizing a construct containing only the second EGF domain of MAD20 type PfMSP1 19 was found in only about 4% of the donors. Neither the prevalence nor the levels of any of the antibody specificities varied significantly with season, age, or sex. Significantly, and in contrast to previous reports from other parts of West Africa, we found no evidence of an association between antibody responses to PfMSP1 19 and clinical protection against malaria.